PERSPECTIVES OF THE USE OF THE CLOUD ORIENTED EDUCATIONAL ENVIRONMENT FOR PROFESSIONAL PREPARATION OF BACHELOR PUBLISHING AND PRINTING - Denisenko С. М. (Journal of Information Technologies in Education (ITE), 2019)
The article is devoted to consideration of the cloud-oriented educational environment as a perspective form of providing educational process in institutions of higher education. The didactic potential and prospects of using the cloud-based educational environment in the professional training of bachelors of publishing and printing specialization «Technologies of electronic multimedia editions». The approaches to the definition of the essence of the concept «cloud technologies» are analyzed and their features are determined. The role of cloud computing technologies in the organization of educational process in modern educational institutions is described. The approaches to the definition of the cloud-oriented educational environment and its potential didactic advantages and possible problems are presented. The significance of such concepts as models, objects and subjects of the cloud-oriented educational environment, cloudoriented training devices, cloud-based tools or applications are revealed. The didactic potential and prospects of using the cloud-based educational environment in the professional training of bachelors of publishing and printing specialization «Technologies of electronic multimedia editions» are considered. It is determined that this is a powerful platform that provides the opportunity to fully use all modern educational resources and tools, in particular, multimedia education. It has been established that the informational and educational environment created on the basis of cloud technologies may not only be a learning environment for bachelors of publishing and printing, but also become a the space of creativity and expression.